AXL Inhibition Represents a Novel Therapeutic Approach in BCR-ABL Negative Myeloproliferative Neoplasms. Issue 9 (11th September 2021) - Beitzen-Heineke, Antonia; Berenbrok, Nikolaus; Waizenegger, Jonas; Paesler, Sarina; Gensch, Victoria; Udonta, Florian; Vargas Delgado, Maria Elena; Engelmann, Janik; Hoffmann, Friederike; Schafhausen, Philippe; von Amsberg, Gunhild; Riecken, Kristoffer; et al.
Abstract : BCR-ABL negative myeloproliferative neoplasms (MPNs) consist of essential thrombocythemia, polycythemia vera, and myelofibrosis. The majority of patients harbor the JAK2 -activating mutation V617F. JAK2 inhibitors were shown to reduce symptom burden and splenomegaly in MPN patients. However, treatment options are limited after failure of JAK2 inhibitors. AXL, a member of the TAM family of receptor tyrosine kinases, mediates survival and therapy resistance of different myeloid cancers including acute myeloid leukemia and chronic myeloid leukemia. We studied the relevance of AXL as a target in MPN using primary patient cells and preclinical disease models. We found that AXL is abundantly activated in MPN cells and that its ligand growth arrest-specific gene 6 is upregulated in MPN patients. Pharmacologic and genetic blockade of AXL impaired viability, decreased proliferation and increased apoptosis of MPN cells. Interestingly, ruxolitinib treatment induced increased phosphorylation of AXL indicating that activation of AXL might mediate resistance to ruxolitinib. Consistently, the AXL inhibitor bemcentinib exerted additive effects with ruxolitinib via impaired STAT3, STAT5, and AKT signaling. Both agents had activity when employed alone and exerted an additive effect on survival and splenomegaly in vivo. Moreover, bemcentinib treatment normalized red blood cell count and hemoglobin levels in vivo. Thus, our data indicate that AXL inhibition represents a novel treatment option in MPN warranting clinical investigation.